Necessary and sufficient conditions for the BRI success - Yongjun Chen; Chenglong Guo (International Studies of Economics)
Abstract This paper presents a general theoretical framework for understanding the Belt‐and‐Road Initiative (BRI). We begin with an introduction to the connotations of the BRI and a review of the initiative's main achievements since its inception. From these achievements, we identify the existence of a potential match between supply and demand in jointly building the BRI to be the foremost necessary condition for win–win cooperation for participating countries. Several features of China's contemporary economic structure are shown to provide the huge potential of supply that matches the massive demand of many Belt‐and‐Road countries for infrastructure development. To unleash the full potential of the BRI, a series of sufficient conditions must be met so that supply and demand interact in a virtuous manner. In the first stage of jointly building the BRI, the key to turn the initiative's potential into reality is to develop the “Five Links” of policy coordination, infrastructure connectivity, unimpeded trade, financial integration, and people‐to‐people bond. Now that the BRI has entered the high‐quality development stage, we demonstrate that China has taken or needs to work on policy measures in 10 areas to ensure the continuing and sustainable success of the BRI construction.